UiTM champions health advocacy on HIV prevention through u-care conference 2025 - Ismail, Ilham Ameera; Zainal Abidin, Aiza Nur Izdihar; Zaki, Muhammad Zahiruddin; Md Shah, Nurfazlinda (Faculty of Medicine, 2025)
Universiti Teknologi MARA (UiTM) continues to strengthen its role in educating and empowering students as agents of public health change with the successful organisation of the U-CARE (University-Community Action on Reducing Epidemic) 2025 Conference. The three-day event was held at the Copthorne Hotel, Cameron Highlands, Pahang, on 20- 22 June 2025.